Treatment of pediatric plasma cell myeloma type post‐transplant lymphoproliferative disorder with modern risk‐directed therapy. Issue 10 (12th June 2018) - Epperly, Rebecca; Ozolek, John; Soltys, Kyle; Cohen, Debra; Goyal, Rakesh; Friehling, Erika
Abstract: Post‐transplant lymphoproliferative disorder (PTLD) related plasma cell neoplasms are rare in pediatric patients. We report a pediatric liver transplant recipient with plasma cell myeloma type PTLD. Cytogenetics included 1q duplication, associated with poor prognosis in adult multiple myeloma, and t(8;14). High‐risk cytogenetics has not been reported in pediatric plasma cell myeloma type PTLD. The patient was treated with bortezomib, dexamethasone, and lenalidomide with subsequent autologous stem cell transplant. He achieved a 6‐year remission, demonstrating tolerance to and efficacy of this modern myeloma regimen in a pediatric patient. Unfortunately, he subsequently died from complications of repeat liver transplant.